Everyday and Exotic Foodborne Parasites - Marilyn B Lee (Canadian Journal of Infectious Diseases, 2000)
Everyday foodborne parasites, which are endemic in Canada, include the protozoans Entamoeba histolytica, Giardia lamblia and Cryptosporidium parvum. However, these parasites are most frequently acquired through unfiltered drinking water, homosexual activity or close personal contact such as in daycare centres and occasionally via a food vehicle. It is likely that many foodborne outbreaks from these protozoa go undetected. Transmission of helminth infections, such as tapeworms, is rare in Canada because of effective sewage treatment. However, a common foodborne parasite of significance is Toxoplasma gondii. Although infection can be acquired from accidental ingestion of oocysts from cat feces, infection can also result from consumption of tissue cysts in undercooked meat, such as pork or lamb. Congenital transmission poses an immense financial burden, costing Canada an estimated $240 million annually. Also of concern is toxoplasmosis in AIDS patients, which may lead to toxoplasmosis encephalitis, the second most common AIDS-related opportunistic infection of the central nervous system. Exotic parasites (ie, those acquired from abroad or from imported food) are of growing concern because more Canadians are travelling and the number of Canada?s trading partners is increasing. Since 1996, over 3000 cases of Cyclospora infection reported in the United States and Canada were epidemiologically associated with importation of Guatemalan raspberries. Unlike toxoplasmosis, where strategies for control largely rest with individual practices, control of cyclosporiasis rests with government policy, which should prohibit the importation of foods at high risk.